Enhancement of the Microbial Dehalogenation of a Model Chlorinated Compound - Jacobson, Stuart N. (1981)
A number of chlorinated aromatic and aliphatic compounds were dehalogenated when incubated with sewage. Preincubating the sewage with nonchlorinated organic substrates enhanced the subsequent dehalogenation of the chlorinated chemicals. Dehalogenation of 4-chloro-3,5-dinitrobenzoic acid (CDBA) in lake water occurred as a result of microbial growth both in the light in the absence of added nutrients and in the dark in the presence of acetate. No organism able to use CDBA as a carbon source was isolated. Axenic bacterial cultures and a nonaxenic Chlamydomonas culture released chloride from CDBA. The metabolism of CDBA by the latter culture, a process that was inhibited by 3-(3,4-dichlorophenyl)-1,1-dimethylurea, yielded a product that was identified as α-hydroxymuconic semialdehyde. This product of an apparent cometabolic transformation was mineralized by a strain of Streptomyces, thus suggesting that certain cometabolic products may not accumulate because they are carbon sources for other species.